Strategies of Growth for Entrepreneurial Ecosystem in Technological Parks: Example of National Technopark - Yüce, Enes; Ulusoy, Tolga (Zenodo, 2022)
It is clear that important developments will be achieved in growth strategies with information, education, governance and wide-ranging reforms in order to create strong foundations. In the entrepreneurship ecosystem; Technoparks provide a business environment that supports entrepreneurship and contribute to local and global change and development. With the many advantages and supports provided to businesses through technoparks, realization of social goals, competition, quality and added value to the country's economy in many aspects are provided. With this aspect, technoparks play an important role in the growth strategies of the businesses they house. The aim of this study; To determine the growth strategies of all companies operating in the technopark and to measure their differences according to demographic characteristics. For this purpose, data were collected from 48 years ago. The data of the research; It was measured by factor analysis, t-test and analysis of variance (ANOVA) and correlation analysis using SPSS. As a result of the research, it was not determined that there were significant differences between the growth strategies of the participants and their demographic characteristics.
Keywords: Entrepreneurship, Enlightened Ecosystem, Technoparks, Growth Strategies; Engineering; Mühendislik; Entrepreneurship; Enlightened Ecosystem; Technoparks; Growth Strategies; 9. Industry and infrastructure; 11. Sustainability; 8. Economic growth; 1. No poverty